THE IMPACT OF PODCASTS ON STUDENTS’ ENGLISH LISTENING PROFICIENCY AND SKILLS IN SMA NEGERI 1 MANADO - Rorintulus, Bravelly; Liando, Nihta V. F.; Tuerah, Ignatius J. C. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research is about the impact of English Podcast on XII Language class student’s English Listening skills. Students of XII Language class in SMA Negeri 1 Manado even though they have decent English listening skills already but there are still some students who don’t possess good English listening skills and find it difficult to understand the videos, while also faces boredom in the teaching learning process. This research uses the Quantitative method as the research method, The sample of this research is 32 Students from the XII Language class in SMA Negeri 1 Manado, the sampling technique used is one group pre-test and post-test, which uses pre-test and post-test as the procedure of collecting the data, The pre-test and post-test includes tasks assessing listening comprehension and vocabulary recognition and uses 3 different types of questions, which is Multiple choice, true or false questions, and fill-in-the-blanks questions. The result of this research showed that Podcast indeed has a positive impact on students of XII Language class English listening skills, this was supported by the fact that the result of the pre-test that was obtained by the researcher showed the mean score of the pre-test 67,81 and 12,57 for the standard deviation which can be categorized as decent and compared to the result of the Post-test the mean score is 85 and the standard deviation is 14,14 which is higher than the pre-test. This means that the use of podcasts was quite effective in enhancing student’s listening skills.